LIPs, orogens and supercontinents: The ongoing saga - Condie, K.C.; Pisarevsky, S.A.; Puetz, S.J. (ELSEVIER, 2021)
Of nine large age peaks in zircon and LIP time series <2300 Ma (2150, 1850, 1450, 1400, 1050, 800, 600, 250 and 100 Ma), only four are geographically widespread (1850, 1400, 800 and 250 Ma). These peaks occur both before and after the onset of the supercontinent cycle, and during both assembly and breakup phases of supercontinents. During supercontinent breakup, LIP activity is followed by ocean-basin opening in some areas, but not in other areas. This suggests that mantle plumes are not necessary for ocean-basin opening, and that LIPs should not be used to predict the timing and location of supercontinent breakups. LIP events may be produced directly by mantle plumes or indirectly from subduction regimes that have inherited mantle-cycle signatures from plume activity. A combination of variable plume event intensity and multiple plume cyclicities best explains differences in LIP age peak amplitudes and irregularities. Peaks in orogen frequency at 1850, 1050, 600 Ma, which approximately coincide with major zircon and LIP age peaks, correspond to onsets of supercontinent assembly, and age peaks at 1450, 250 and 100 Ma correspond to supercontinent stasis or breakup. Although collisional orogens are more frequent during supercontinent assemblies, accretionary orogens have no preference for either breakup or assembly phases of supercontinents. A sparsity of orogens during Rodinia assembly may be related to incomplete breakup of Nuna as well as to the fact that some continental cratons never accreted to Rodinia. There are three groups of passive margins, each group showing a decrease in duration with time: Group 1 with onsets at 2.2–2.0 Ga correspond to the breakup of Neoarchean supercratons; Group 2 with onsets at 1.5–1.2 Ga correspond to the breakup of Nuna; and Group 3 with onsets at 1.5–0.1 Ga not corresponding to any particular supercontinent breakup. New paleogeographic reconstructions of supercontinents indicate that in the last 2 Gyr average angular plate speeds have not changed or have decreased with time, whereas the number of orogens has increased. A possible explanation for decreasing or steady plate speed is an increasing proportion of continental crust on plates as juvenile continental crust continued to be added in post-Archean accretionary orogens. Cycles of mantle events are now well established at 90 and 400 Myr. Significant age peaks in orogen frequency, average plate speed, LIPs and detrital zircons may be part of a 400-Myr mantle cycle, and major age peaks in the cycle occur near the onset of supercontinent assemblies. The 400-Myr cycle may have begun with a “big bang” at the 2700 Ma, although the LIP age spectrum suggests the cycle may go back to at least 3850 Ma. Large age peaks at 1850, 1050, 600 and 250 Ma may be related to slab avalanches from the mantle transition zone that occur in response to supercontinent breakups.